The low down on sphingosine-1-phosphate lyase as a regulator of thymic egress - Saba, Julie D. (J Immunol Sci, 2017)
After undergoing positive and negative selection in the thymus, surviving mature T cells egress from the thymic parenchyma and enter the bloodstream to participate in adaptive immunity. Thymic egress requires signals mediated by sphingosine-1-phosphate (S1P), a bioactive lipid that serves as the ligand for a family of G protein-coupled receptors (S1P1-5) expressed on many cell types, including T cells. In the final stage of their development, T cells upregulate S1P1 expression on the cell surface, which enables them to recognize and respond to a chemotactic S1P gradient that lures them into the bloodstream. The gradient is generated by an S1P source close to the site of egress combined with an S1P sink generated by the actions of S1P catabolic enzymes including S1P lyase (SPL), the only enzyme that irreversibly degrades S1P. The requisite contribution of SPL to thymic egress is demonstrated by the profound lymphopenia observed in SPL knockout (KO) mice and wild type mice treated with SPL inhibitors. SPL is robustly expressed in thymic epithelial cells (TECs), which make up the stromal reticular network of the thymus. However, TEC SPL was recently found to be dispensable for thymic egress. In contrast, deletion of SPL in dendritic cells (DCs) — which represent only a small percent of thymic stroma — disrupts the S1P gradient and blocks thymic egress. These recent observations identify DCs as homeostatic regulators of thymic export through the actions of SPL, thereby adding one more piece to the complex puzzle of how S1P signaling contributes to the regulation of T cell trafficking.